Implementing a national program to reduce catheter-associated urinary tract infection: a quality improvement collaboration of state hospital associations, academic medical centers, professional societies, and governmental agencies - Fakih, Mohamad G; George, Christine; Edson, Barbara S; Goeschel, Christine A; Saint, Sanjay (Infection control and hospital epidemiology, 2013)
Catheter-associated urinary tract infection (CAUTI) represents a significant proportion of healthcare-associated infections (HAIs). The US Department of Health and Human Services issued a plan to reduce HAIs with a target 25% reduction of CAUTI by 2013. Michigan's successful collaborative to reduce unnecessary use of urinary catheters and CAUTI was based on a partnership between diverse hospitals, the state hospital association (SHA), and academic medical centers. Taking the lessons learned from Michigan, we are now spreading this work throughout the 50 states. This national spread leverages the expertise of different groups and organizations for the unified goal of reducing catheter-related harm. The key components of the project are (1) centralized coordination of the effort and dissemination of information to SHAs and hospitals, (2) data collection based on established definitions and approaches, (3) focused guidance on the technical practices that will prevent CAUTI, (4) emphasis on understanding the socioadaptive aspects (both the general, unit-wide issues and CAUTI-specific challenges), and (5) partnering with specialty organizations and governmental agencies who have expertise in the relevant subject area. The work may serve in the future as a model for other large improvement efforts to address other hospital-acquired conditions, such as venous thromboembolism and falls.